Fiscal reforms that work - McDermott, C. John (IMF WashingtonUS, 1996)
Looks at the dynamics between deficit reduction and economic growth. Uses the experience of fiscal consolidation in industrial countries over 1970-95 to examine the interplay between fiscal change and economic performance and to see if the theory of positive expectations has any substance.